INCREASING STUDENT UNDERSTANDING ON PPKN STUDY THROUGH THE DEBATE MODEL TO THE LEGISLATION MATERIALS IN CLASS VIII A SMP NEGERI 4 BANDUNG - Yatti Rosmiati (Jurnal Administrasi Pendidikan, 2023)
This Classroom Action Research aims to improve learning outcomes and activities of class VIII A students in PPKn lessons on legislative material through the application of debate model learning. The results of the pre- study obtained an average value of 55.87, complete 2 people or 5% The results of the research that have been carried out, in the first cycle obtained an average value of 75.06 categorized as “Good” completed 22 people or 55% After reflection, the acquisition of the average value in the second cycle increased, to 86.34 categorized as “Very Good” completed 38 people or 95%. The increase in the average value from the pretest to the first cycle ranges from 19.19 The increase in the percentage of achievement of the KKM value from pretest to cycle 1 ranged from 50% It can be concluded that the application of the debate learning model is effectively used in the learning process of PPKn on legislative matterial because can significantly increase activities, and student learning outcomes. The obstacles found in this study are 1}requires time, extra energy, and patience from the teacher, 2) and overall monitorig and guidance is neededKeyword: Civic Education, Learning Models Debate, Legislation